Pengembangan Media Pembelajaran Articulate Storyline untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar di Masa Pandemi Covid 19 - Eli Mufidah; Nikmatul Khori (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
The general objective of this research and development is to produce a product in the form of an Articulate Storyline learning media that is feasible and effective to improve the learning outcomes of elementary school students during the covid 19 pandemic. The form of research used by the researcher is descriptive with qualitative and quantitative data analysis. This type of research is Research and Development, which refers to the Borg and Gall model, with media development specifications covering 10 stages. The results of the research on the development of the Articulate Storyline learning media show that the qualification level of the Articulate Storyline learning media product meets the very valid criteria with the results of the material expert test of 90%, the learning media expert test of 84.7%, the practicality test by the learning practitioner of 88.8% and field trial by 95%. Meanwhile, the qualification level of the Articulate Storyline learning media product effectiveness level in improving student learning outcomes meets the high criteria. This shows that the product developed has a qualification level of feasibility and effectiveness according to the student's condition, so that this media is feasible and effective to use in distance learning (PJJ).